Overexpression and knock-down studies highlight that a disintegrin and metalloproteinase 28 controls proliferation and migration in human prostate cancer. Issue 40 (October 2016) - Rudnicka, Caroline; Mochizuki, Satsuki; Okada, Yasunori; McLaughlin, Claire; Leedman, Peter J.; Stuart, Lisa; Epis, Michael; Hoyne, Gerard; Boulos, Sherif; Johnson, Liam; Schlaich, Markus; Matthews, Vance
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Prostate cancer is one of the most prevalent cancers in men. It is critical to identify and characterize oncogenes that drive the pathogenesis of human prostate cancer. The current study builds upon previous research showing that a disintegrin and metallproteinase (ADAM)28 is involved in the pathogenesis of numerous cancers. Our novel study used overexpression, pharmacological, and molecular approaches to investigate the biological function of ADAM28 in human prostate cancer cells, with a focus on cell proliferation and migration. The results of this study provide important insights into the role of metalloproteinases in human prostate cancer. The expression of ADAM28 protein levels was assessed within human prostate tumors and normal adjacent tissue by immunohistochemistry. Immunocytochemistry and western blotting were used to assess ADAM28 protein expression in human prostate cancer cell lines. Functional assays were conducted to assess proliferation and migration in human prostate cancer cells in which ADAM28 protein expression or activity had been altered by overexpression, pharmacological inhibition, or by siRNA gene knockdown. The membrane bound ADAM28 was increased in human tumor biopsies and prostate cancer cell lines. Pharmacological inhibition of ADAM28 activity and/or knockdown of ADAM28 significantly reduced proliferation and migration of human prostate cancer cells, while overexpression of ADAM28 significantly increased proliferation and migration. ADAM28 is overexpressed in primary human prostate tumor biopsies, and it promotes human prostate cancer cell proliferation and migration. This study supports the notion that inhibition of ADAM28 may be a potential novel therapeutic strategy for human prostate cancer.